Fertilization strategies for cotton planted in coastal severe saline-alkali soils based on irrigation with saline water in winter - YANG Lilin; YU Haiying; HOU Jianwei; ZHU Xiangmei (浙江大学学报. 农业与生命科学版)
This study focused on exploring the optimal fertilization strategies for cotton planted in coastal severe saline-alkali soils based on irrigation with saline water in winter. A four-year positional experiment was conducted on cotton based on irrigating saline water in lower plain of Hebei, including fertilizer types (controlled-release/loss-control fertilizer and traditional fertilizer), fertilization modes (application once as base fertilizer, application twice as base and topdressing fertilizer, respectively) and fertilization rates (high and low amount). The results showed that the salinity of 0-20 cm soil depth was reduced to less than 2.0 g/kg during the sowing seasons in spring as a result of irrigating saline water, which ensured germination and emergence of cotton seeds. In terms of fertilizer type, the first choice for planting cotton was the loss-control fertilizer that containing N-P-K and attapulgite in the severe saline-alkali area, and applied once as base fertilizer. Whether the traditional fertilizer mix was used, the potassium sulfate fertilizer was necessary besides urea and superphosphate, and all fertilizers should be applied once as base fertilizer before sowing. Given equal amount of nitrogen, urea applications once as base fertilizer had a significant increase in cotton yield, compared with twice application as base and topdressing fertilizer. Moreover, the latter could result in risks of soil inorganic-N accumulation and saline content increase after harvest. Excessive fertilizer application inhibited cotton seedling and plant growth during the early growing stage, and then influenced cotton yield at last. So the fertilization strategies for cotton planted in coastal severe saline-alkali area in North China were as follows: during the winter freezing period before sowing, local underground salt water was extracted for irrigation, and the irrigation amount was 100-180 mm; the reasonable amount of fertilizer applied once before sowing in spring was 169 kg/hm2 N, 65 kg/hm2 P2O5, and 78 kg/hm2 K2O; and the fertilizer dosage form should be preferred to loss-control fertilizer. Under the optimal fertilization strategies, the seed cotton yield in the severe saline-alkali soils could reach to 3.0-3.2 t/hm2. The above results provide theoretical basis and technical support for the development and utilization of saline-alkali soils and its underground salt water resources, as well as fertilizer saving, yield increasing, and the green and efficient planting of salt-tolerant cotton.